Survival is negatively related to basal metabolic rate in tropical Andean birds. (5th June 2019) - Scholer, Micah N.; Arcese, Peter; Puterman, Martin L.; Londoño, Gustavo A.; Jankowski, Jill E.
Abstract: Life‐history theory postulates that physiological traits, such as energy metabolism, can be understood in terms of allocation trade‐offs between self‐maintenance and reproduction over an organism's life span, and data show that metabolic intensity and survival vary inversely with latitude, with tropical birds exhibiting a "slow" pace of life relative to temperature species. However, tropical regions harbour strong environmental gradients of their own, and it remains to be shown whether similar life‐history trade‐offs between metabolism and longevity are reflected among tropical birds of the same latitude. We estimated apparent annual survival in 37 species of tropical passerine birds along an elevational gradient (400–3, 000 m) in Peru to test whether variation in survival was influenced by basal metabolic rate (BMR; estimated at the same sites), elevation or both factors. We used path analysis to test our prediction that survival would decline as BMR increased, while accounting for the potential direct effects of elevation on survival due to differences in predation pressure or environmental conditions as well as potential indirect effects of elevation on BMR via temperature and the costs of thermoregulation. Higher BMR in tropical passerine birds predicted lower apparent survival, regardless of the elevation at which species occurred. In addition, elevation had a direct negative effect on apparent survival, perhaps due to harsher abiotic conditions, low site fidelity or both at high elevations. We provide evidence of a link between metabolic rate and longevity previously undescribed in populations of free‐living birds. Our results illustrate that tropical montane species may be characterized by a unique suite of traits in their pace of life, in which BMR does not differ from lowland birds, but survival does. Aplain language summary is available for this article. Abstract : Plain Language Summary